Virtual Learning Environments: Modeling a New Learning Policy Strategy - Sergejus Neifachas; Tomas Butvilas; Kristina Kovaitė (Acta Paedagogica Vilnensia, 2022)
The paper examines the modelling dimension of the virtual teaching/learning environment and its implementation practices. Changing trends of the educational processes become apparent; thus, it is necessary to reflect and justify the contours of modeling the virtual educational environment. When looking for new ways of conceptualizing teaching/learning strategies, it is especially important to understand the inclusive, enabling context of the open learning spaces, to adequately assess the content elements and to predict the possible characteristics of their expression in the context of inclusive and sustainable economy. In this paper, the process of modeling the virtual learning environment is analyzed using reflexive approaches. It is stressed that the aim of the new education policy strategy is to create learning environments that enable people of different talents and interests to receive appropriate learning, adapt to different life situations and goals, and reconcile, say, formal learning and self-education. Qualitative data is presented along with both teachers’ and educational experts’ attitudes.